Experimental study on the correlation between pore evolution characteristics and seepage flow of loaded lignite - Xi Zhang; Xi Zhang; Yankun Ma; Yankun Ma; Mingye Hu; Aohan Zhao; Aohan Zhao; Wenwang Yang; Wenwang Yang (Frontiers in Earth Science)
The pressure on coal affects the pore fracture structure, altering the seepage characteristics of fluids such as gas or water. A special pseudo-triaxial loading nuclear magnetic gripper was used for uniaxial compression testing of the coal body. The T2 map of the lignite was tested online, and MRI imaging was performed. The correlation between the pore fracture structure evolution and seepage characteristics of lignite was studied. The results show that (1) there are three stages, namely, compression, pore development, and post-peak failure, which promote the development and evolution of medium pore and macropores in lignite. (2) Under uniaxial compression, the permeability of the lignite sample shows a “V-shaped” trend, first decreasing and then increasing. When the axial pressure reaches approximately 3.0 MPa, the mutation of the MRI signal increases, and the enhancement of the MRI signal of the sample is due to the cumulative effect of mutation after aggregation. The aggregation of water image signals reflects the distribution area of pores that dominate seepage. (3) Under uniaxial compression, the pore change rate Si slightly decreased. The pore change rate Si of medium pores and macropores showed a positive correlation with axial pressure, which is consistent with the total pore change trend. The compressibility coefficient Cp of the porous pores (medium pores and macropores) and the permeability stress sensitivity coefficient Cf exhibited a linear correlation. The fractal dimension D2 and D3 values of pores in the medium and macropores scale range are close to 3, with the maximum value of D2 being 2.971. This indicates significant fractal characteristics, suggesting that medium pores are the most developed in this scale range. Researches show that that the middle pore has a greater stress sensitivity and shows obvious fractal characteristics during the load failure. The compressibility of the large pore is correlated with the permeability sensitivity, These results show can help elucidate the influence of the pores fracture structure on the seepage evolution of lignite.